Promoting peace and equality through the practice of good Islamic governance: the case of Islamic finance - Hassan, Rusni; Mohamad Noor, Fatimah Azzahra (Ssskr Innani Mahavidyalaya.karanja, 2021)
The aim of this article is to examine the idea of good governance in Islamic finance (IF) practice and how it may contribute to the development of peace and equality within a community. Many have perceived that as a financial system, Islamic finance only focuses on commercial aspects or profit maximisation. This may not be the case, however, with Islamic financing. Islamic finance lays a premium on enhancing human well-being, social justice, and fair commercial relations. It recognizes the critical nature of environmental protection and prohibits reckless profiting at the cost of others or investing in enterprises that may cause harm to our society. The element of ibqa’ (promoting good) and hifz (preventing harm) are the fundamental principles of Shariah in Islamic finance. This research is a qualitative studythat uses documentary analysis method. The data is gathered from primary and secondary data.According to the study's results, Islamic finance hassufficiently upheld the concept of Islamic good governance through Shariah governance framework. The application of Islamic good governance is observable in the practice of Shariah Governance Framework 2010. However, in the aspect of promoting peace and equality within a society as part of achieving a comprehensive human development and Maqasid Shariah,the contribution of Islamic financial institutions (IFIs) is still lacking. Even though several initiatives have been taken by some IFIs to expand their role in the society particularly in the sustainability agenda, the result is still insignificant due to several challenges in its implementation.